Stealth multiboson signals - J. A. Aguilar-Saavedra (European Physical Journal C: Particles and Fields, 2017)
Abstract We introduce the ‘stealth bosons’ S, light boosted particles with a decay $$S → AA → q \bar{q} q \bar{q}$$ S→AA→qq¯qq¯ into two daughter bosons A, which subsequently decay into four quarks that are reconstructed as a single fat jet. Variables that measure the two-pronged structure of fat jets, which are used for diboson resonance searches in hadronic or semi-leptonic final states, classify the jets produced in stealth boson decays as QCD-like – actually, for these variables they may seem more background-like than the QCD background itself. The number of tracks in those jets can also be, on average, much higher than for the fat jets arising from the hadronic decay of boosted W and Z bosons. Therefore, these elusive particles are hard to spot in standard searches. Heavy resonances decaying into two such stealth bosons, or one plus a W / Z boson, could offer an explanation for the recurrent small excesses found in hadronic diboson resonance searches near an invariant mass of 2 TeV.